Housing prices in Spain: Convergence or decoupling? - Corinna Ghirelli; Danilo Leiva-León; Alberto Urtasun (SERIEs - Journal of the Spanish Economic Association, 2023)
In this article, we measure changes in the synchronization of housing price cycles across Spanish cities over time. We rely on a regime-switching framework that identifies the housing price cycles of pairs of cities and simultaneously infers the evolving relation between those cycles. These bilateral relationships are then summarized into an aggregate index of city-level housing cycle synchronization. The estimates suggest that Spanish housing prices have followed a convergence pattern that reached a peak in 2009 and decreased slightly afterward. We also identify the cities that have been the main contributors to this convergence process. Moreover, we show that differences in population growth and economic structure are key factors in explaining the evolution of housing price synchronization among Spanish cities.
Keywords: C32; E31; R11; 330; Housing cycles; Spain; Synchronization